Passage of Coronavirus Infection in Patients with Diabetes and its Prevention - Yusupova Mamlakat Mutalibovna (Genius Journals, 2023)
The article summarizes the medical history and statistics of 58 patients treated in the hospital during the coronavirus pandemic in 2019-2022. Clinical manifestations are discussed depending on the date and diagnostic methods. Post-treatment statistics and results are presented..
Keywords: diabetes; coronavirus; complications; prevention